Cyclic tetra- and hexaynes containing 1,4-donor-substituted butadiyne units: synthesis and supramolecular organization - Werz, Daniel B.; Gleiter, Rolf; Rominger, Frank (The journal of organic chemistry, 2004)
Cyclic bis(1,3-butadiynes) with sulfur centers placed in the α-position to the 1,3-butadiyne units (2(n)) were synthesized by Glaser coupling of the corresponding open chain dithia-α,ω-diynes 1(n). In a second protocol we applied a four-component cyclization by reacting α,ω-dithiocyanatoalkanes 6(n) or α,ω-diselenocyanatoalkanes 7(n) with dilithium-1,3-butadiynide. This concept afforded either the cyclic dimers (S, 2(n); Se, 9(n)) or the cyclic trimers (S, 8(n); Se, 10(n)). Most of the molecular structures of 2(n) and 9(n) adopt chairlike conformations in the solid state. Tubular structures in the solid state with short distances between the chalcogen centers of neighboring stacks were encountered for 2(5), 9(5), 8(4), 10(4), and 10(5). Recrystallization of 10(5) from various polar and nonpolar solvents yielded inclusion of the solvent guest molecules. The solvent-accessible volume was calculated to vary from 19% (n-hexane) to 25% (mesitylene). The elastic properties of our cycles are due to the flexible methylene chains and the easily variable torsional angles between the rigid 1,3-butadiyne rods.